A review on recent available positioning technologies and its advancement - Chai, Nee Ping; Wan Azlan, Wan Zainal Abidin; Wan Hashim, Wan Ibrahim; Kismet, Anak Hong Ping (Malaysian Abstracting and Indexing System, 2015)
This paper reviews and compares the available positioning technology for location based application such as the Intelligent Transport System (ITS) and personal vehicle positioning. With the rapid growing trend of worldwide vehicle ownership, issues such as traffic congestion, environmental pollution, energy consumption and road accident cases are increasing. Intelligent Transportation System (ITS) which depends on location and positioning has been identified as one of the advocated key to resolve the issues. Global Positioning System (GPS) is one of the most promising ubiquitous positioning technologies accepted worldwide for ITS application. It is discerned that GPS alone in ITS application is not adequate since GPS faced Non-Line-of-Sight (NLOS) and multipath effect. New technology integrated is needed to overcome the drawback of the current system for continuous positioning; particularly important for ITS application to be fully functional. This is the significant motivation for tremendous research works had been carried out to improve the performance of positioning. In this paper, advantages and disadvantages of the recent available positioning technologies being used in the implementation of ITS such as satellite-based positioning, network-based positioning and location integration of several positioning technologies is found to be able to improve accuracy, reliability, availability and applicability of the ITS.